PENYIMPANGAN FUNGSI DAN NILAI-NILAI PANCASILA DALAM PENEGAKAN HUKUM SEBAGAI PEDOMAN HIDUP DALAM BERMASYARAKA - Ervina Dwi Indriastuti (JURNAL ILMIAH HUKUM DAN DINAMIKA MASYARAKAT, 2018)
Pancasila has become the agreement of the Indonesian people as the basis of theUnitary State of the Republic of Indonesia, but in its implementation effortsexperience various obstacles both internal and external. Pancasila as a view of thenation's life needs to be implemented in real life, this has been exemplified by thefounding fathers of the nation through hard work and struggle to produce Indonesianindependence. Concern for the legal conditions that are in favor so far from theelement of justice makes the mind interested in discussing whether the values taughtby Pancasila are still heeded or ignored. Pancasila which is the nation's ideology asa view of life and the foundation in the activities of society, nation and state isimpressed only to be memorized without application, including in the field of law. Thequality of the state which is the benchmark for safeguarding the nation's ideology iseagerly awaited to control the implementation of a just law based on the noble valuesof Pancasila. Pancasila as the basis of the State is based as a source of law inIndonesia. All laws and regulations must be an elaboration of the principlescontained in Pancasila. All laws and regulations that are not in accordance withPancasila, are null and void. Therefore, to be able to understand the accuracy of lawsand regulations, it is necessary to understand the concepts, principles and valuescontained in Pancasila. Pancasila as the basis of the state is implemented to be alegal norm that is compelling, binding and sanctions.